Pengaruh Islam dalam Kebudayaan Melayu - Hakimi Arsya; Badrun (Medan Resource Center, 2022)
This article aims to discuss how the influence of Islam in Malay culture. Islam and Malay are two interrelated elements. The two cannot be separated. In writing and compiling this article, the historical approach method is used which consists of four stages, namely the first heuristic as a tool for collecting sources, the second for verification functions to criticize the sources obtained, the third for interpretation to function as interpreting the sources obtained so that they can be used in writing history. and the last is historiography. The results of the study show that the Malay people are open to people who come to their country, thus facilitating cultural diffusion. The Islamization of the Archipelago occurs through channels; trade, marriage, government bureaucracy, tasawuf and tarekat knowledge, education and the arts. The Muslim community in Tanah Melayu initially embraced Islam because of the completeness and beauty of Islam itself which made its adherents better than other people.